The Influence of Digital Literacy of Small Business Actors on The Level of E-Commerce Use in Blitar District - Siti Azizah; Arifatus Sholikhah; Irfan H. Djunaidi; Diah Priharsari; Mas Ayu Ambayoen; Siti Hamidah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
MSME entrepreneurs assisted by the Livestock and Fisheries Service in Blitar Regency are classified as independent MSMEs on a household scale, so it is necessary to market e-commerce to achieve a national economy that can improve the welfare of business actors and the community. This research was conducted on MSME business actors assisted by the Livestock and Fisheries Service from several OPS MSME members, PPMK Srikandi, AKBest product business actors, and mothers of